2019
DOI: 10.1108/ijhma-03-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of negative information on the volatility of real estate residential prices in Abuja, Nigeria

Abstract: Purpose The purpose of this paper is to determine the effect of negative information on the volatility of real estate residential prices in Abuja, Nigeria. Design/methodology/approach The empirical research covers a sample period of 17 years from the first quarter of 2000 to the fourth quarter of 2017. The leverage effect of Abuja’s real estate residential price volatility is determined. Exponential generalised autoregressive conditional heteroscedasticity is used to determine the ARCH shock, GARCH persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Crucially, countries with lower uncertainty levels tend to attract more foreign direct inflows (FDI) (Nguyen and Lee, 2021). Based on these indications that emerging and frontier property markets are more susceptible to uncertainty fluctuations, a glaring gap remains for scholarly works to explore the specific effects of economic uncertainty in these markets (Alkali et al ., 2019; Sadayuki et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, countries with lower uncertainty levels tend to attract more foreign direct inflows (FDI) (Nguyen and Lee, 2021). Based on these indications that emerging and frontier property markets are more susceptible to uncertainty fluctuations, a glaring gap remains for scholarly works to explore the specific effects of economic uncertainty in these markets (Alkali et al ., 2019; Sadayuki et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…255) enunciated that "Price determination in the property market is often fraught with irrational behaviour and trends cannot be explained by fundamental drivers of the sector". And the effects of negative information on the volatility of real estate from data emanating from 2000Q1 to 2017Q4 was also documented by (Alkali, Sipan, & Razali, 2019). Freybote, (2016) established with the help of monthly data from 2010 to 2013 that REIT bond yield are negatively related to sentiment regardless of the credit rating and the S&P index inclusion.…”
Section: Market Sentiment Measurement and House Pricesmentioning
confidence: 88%
“…Hence the need to increase the supply of housing development. The author observed that macroeconomic variables impact on rental and housing prices predominate previous studies (Khalid et al, 2012;Olowofeso & Oyetunji, 2016;Olatunji et al, 2017;Alkali et al, 2020). Whereas the impact on housing development which in turns affect the housing market and prices earns insufficient scientific attention.…”
Section: Introductionmentioning
confidence: 91%